The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/admt.202301246
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Deep Discharge Induced Asymmetric Copper Deposition in Lithium‐Ion Cells by Operando Synchrotron X‐Ray Tomography

Shahabeddin Dayani,
Henning Markötter,
Jonas Krug von Nidda
et al.

Abstract: Lithium‐ion cells connected in series are prone to an electrical safety risk called overdischarge. This paper presents a comprehensive investigation of the overdischarge phenomenon in lithium‐ion cells using operando nondestructive imaging. The study focuses on understanding the behavior of copper dissolution and deposition during overdischarge, which can lead to irreversible capacity loss and internal short‐circuits. By utilizing synchrotron X‐ray computed tomography (SXCT), the concentration of dissolved and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…Discharge below the end-of-discharge voltage can result in Cu dissolution from the anode current collecting foil. 163,164,[199][200][201][202][203] Cu dissolution to Cu 2+ or Cu + gets thermodynamically allowed when the anode potential increases above 3.38 V or 3.56 V vs Li/Li + , respectively. 164 Furthermore, Flügel et al showed for seven types of commercial cells, that the additional discharge from the end-ofdischarge voltage to 0 V leads only to minor decreases of cell energy corresponding to negative SOCs of −3% to −9%.…”
Section: Workflows For Detection Of LI Depositionsmentioning
confidence: 99%
“…Discharge below the end-of-discharge voltage can result in Cu dissolution from the anode current collecting foil. 163,164,[199][200][201][202][203] Cu dissolution to Cu 2+ or Cu + gets thermodynamically allowed when the anode potential increases above 3.38 V or 3.56 V vs Li/Li + , respectively. 164 Furthermore, Flügel et al showed for seven types of commercial cells, that the additional discharge from the end-ofdischarge voltage to 0 V leads only to minor decreases of cell energy corresponding to negative SOCs of −3% to −9%.…”
Section: Workflows For Detection Of LI Depositionsmentioning
confidence: 99%